PRAKTIK BAHASA INGGRIS KONTEKSTUAL SERTA MANAJEMEN STRES PADA PEMBELAJARAN TATAP MUKA ERA KENORMALAN BARU - Pranoto, Yohanes Heri; Inharjanto , Anselmus; Leovani, Ega; Clara, Catharina; Heru Ismadi, Florentinus (Jurnal Abdimas Musi Charitas, 2022)
The initial process of face-to-face learning that occurs at the beginning of the school year requires adequate preparation both physically and mentally for students. Not infrequently the initial process causes stress and eventually triggers conflict, both between individuals and groups. On the other hand, learning must continue and the competency of the predetermined subject does not experience problems in being delivered. The purpose of this PKM activity is to integrate 2 materials in one flow of activity: stress management with one of the lessons, namely English. Activities are scheduled in 4 meetings with seminary students in Rethorica A and B classes as participants. Total participants were 33 people. The results of the activity showed positive results and responses from all participants which were shown from the pretest and posttest scores and the feedback questionnaire. The experience of learning contextual English and awareness of the causes and effects of stress can provide meaningful input from the learning process and self-management for prospective priests.